2014
DOI: 10.1038/gim.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

Patient decisions for disclosure of secondary findings among the first 200 individuals undergoing clinical diagnostic exome sequencing

Abstract: Purpose:Exome sequencing of a single individual for a clinical indication may result in the identification of incidental deleterious variants unrelated to the indication for testing (secondary findings). Given the recent availability of clinical exome testing, there is a limited knowledge regarding the disclosure preferences and impact of secondary findings in a clinical diagnostic setting. In this article, we provide preliminary data regarding the preferences for secondary findings results disclosure based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
91
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 38 publications
12
91
0
4
Order By: Relevance
“…[23][24][25] Stimulating the development of educational materials that clearly communicate disease associations or the development of decision tools for patients and physician's is an open research field. 14,26 Further research is needed to compare different ways of disclosing results, also from patients' perspective and preferences in this field of rapid evolving NGS strategies in daily practice.…”
Section: Discussion Of Current Recommendations In the Literaturementioning
confidence: 99%
“…[23][24][25] Stimulating the development of educational materials that clearly communicate disease associations or the development of decision tools for patients and physician's is an open research field. 14,26 Further research is needed to compare different ways of disclosing results, also from patients' perspective and preferences in this field of rapid evolving NGS strategies in daily practice.…”
Section: Discussion Of Current Recommendations In the Literaturementioning
confidence: 99%
“…The selection of these 56 genes is relied on pathogenicity and the possibility of the genetic result leading to a specific therapeutic option ("actionable" findings). However, there is an in time discussion how to best proceed with incidental findings 72,73 . Whereas in the research setting, these incidental findings usually do not absorb much attention, it is notable that there is growing intrigue in receiving information about incidental findings on the patient side 73 .…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…However, there is an in time discussion how to best proceed with incidental findings 72,73 . Whereas in the research setting, these incidental findings usually do not absorb much attention, it is notable that there is growing intrigue in receiving information about incidental findings on the patient side 73 . This is also reflected by the increasing providing and popularity of direct-to-consumer genetic testing (DTCGT).…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…Whether testing for adult-onset disorders in children, and by deduction prenatally, should be limited is a matter of debate on its own (Mand et al 2012;Anderson et al 2014), but existing guidelines were directed toward actively seeking testing for adult-onset conditions and predated the era of genome-wide sequencing with its potential to uncover such findings incidentally and unintentionally. Recent survey studies have indicated that probands and parents of children undergoing WES are interested in having incidental findings disclosed (Townsend et al 2012;Fernandez et al 2014;Shahmirzadi et al 2014).…”
Section: Management Of Incidental Findingsmentioning
confidence: 99%